Disturbances in Calcium Homeostasis Promotes Skeletal Muscle Atrophy: Lessons From Ventilator-Induced Diaphragm Wasting - Hyatt, Hayden W.; Powers, Scott K. (Frontiers in Physiology, 2020)
Mechanical ventilation (MV) is often a life-saving intervention for patients in respiratory failure. Unfortunately, a common and undesired consequence of prolonged MV is the development of diaphragmatic atrophy and contractile dysfunction. This MV-induced diaphragmatic weakness is commonly labeled “ventilator-induced diaphragm dysfunction” (VIDD). VIDD is an important clinical problem because diaphragmatic weakness is a major risk factor for the failure to wean patients from MV; this inability to remove patients from ventilator support results in prolonged hospitalization and increased morbidity and mortality. Although several processes contribute to the development of VIDD, it is clear that oxidative stress leading to the rapid activation of proteases is a primary contributor. While all major proteolytic systems likely contribute to VIDD, emerging evidence reveals that activation of the calcium-activated protease, calpain, plays a required role. This review highlights the signaling pathways leading to VIDD with a focus on the cellular events that promote increased cytosolic calcium levels and the subsequent activation of calpain within diaphragm muscle fibers. In particular, we discuss the emerging evidence that increased mitochondrial production of reactive oxygen species promotes oxidation of the ryanodine receptor/calcium release channel, resulting in calcium release from the sarcoplasmic reticulum, accelerated proteolysis, and VIDD. We conclude with a discussion of important and unanswered questions associated with disturbances in calcium homeostasis in diaphragm muscle fibers during prolonged MV.